Analisis Faktor-Faktor Yang Mempengaruhi Penundaan Pengiriman Barang Melalui Jalur Laut - Aditya W Utama (JURNAL CITRA WIDYA EDUKASI, 2018)
The role of freight forwarders in the transportation sector is increasingly important in line with the fluctuating volume of freight shipments. The role is in terms of handling the consolidation of cargo, which is the collection of several shipments of cargo from several shipper to several consignees into one vehicle unit to the destination. This is done because the shipper prefers to deal with only one party who will take over all responsibilities, ie since the cargo is delivered to the shipping warehouse until the cargo is received at the receiving warehouse (one stop shipping). Consolidation provides door to door service that is not carried out by shipping companies. The purpose of this research is to find out what factors influence the delay of cargo shipping by shipping line to PT Pancakarsa Bangun Reksa Medan. The type of data collected in this study is primary data which is the data obtained from the results of direct observation in the field of the object under study. The data is a packing list, a bill of lading and an insurance policy. The results showed that the delay in the cargo shipping to customers was caused by several factors, namely: 1) internal factors consisting of humans, methods and leadtime; and 2) external factors consisting of the environment and tools.